Integrated mathematical model based on a heuristic method for loading and routing of vehicles: application in a tobacco company - Moya, Jorge Israel Frómeta; Velázquez, Daniel René Tasé; Mastrapa, Lorena Hernández; León, Yosvany Orlando Lao (Independent Journal of Management & Production, 2020)
The vehicle-routing problem (VRP) combined with freight-loading problem is a complex and relatively recent issue studied by the scientific literature. This paper presents the formulation of a mathematical model and a procedure to solve this problem in a Cuban tobacco company aiming to determine the quantity of merchandise to be loaded on vehicles and the best route to be taken. For this purpose, a decomposition’s heuristic method was used and it was integrated with multiobjective programming by-goals and mixed binary quadratic programming. This approach allowed simplifying the problem and offering a satisfactory solution based on the demand fulfillment, the vehicles’ rational use and for searching the local optimums of the traffic load indicator. The model was tested in a case study and its feasibility evaluated based on a real operational situation in a tobacco company. Although the results of the application of the developed model does not imply reaching the optimal solution to the problem studied, it represents an opportunity for company’s performance improvement and it could be adapted and applied to other institutions dedicated to the same activities.